SOCIAL SUPPORT SOURCES AND ITS IMPACT ON DEPRESSION AND QUALITY OF LIFE AMONG UNIVERSITY STUDENTS - SIYAL, FJ; JISKANI, SA; MURTAZA, A; GUL, ARAA; BHATTI, SF; CHANDIO, P; DUA E SURAYA , S; SIYAL, S; NADEEM, .; ABBAS, W; SHAIKH, ZA; MALIK, E; et al. (Biological and Clinical Sciences Research Journal, 2023)
Depression is considered one of the most common health problem worldwide. It also causes disabilities and affects both males and females globally. Young adults experience university life to develop the latest skills, capabilities, and proficiencies, analyze social networks, and attain knowledge. Due to changes in lifestyle, relationships, and community, and many students feel stress while attending university. This study addresses such issues by evaluating the impact of various social support sources on mental health symptoms and quality of life among university students. This was a cross-sectional survey conducted on university students of Larkana for 6 months. Students of universities were included. Online questionnaire was prepared and was circulated among students. Informed consent was taken from all participants before filling out the questionnaire. The data was entered and analyzed using SPSS 24.0. Mean and standard deviation were measured for quantitative variables (i.e., age). While for qualitative variables (i.e. sociodemographic parameters), frequency and percentage was were measured. A total of 360 responses were collected from university students. The mean age of participants was 23.03 ± 3.91 years. Number of female students was higher (214/59.44%). The majority of the students responded the availability was in a moderate ratio. Most students (165/45.8%) said that they previously experienced depression symptoms, while reminder said they are currently facing symptoms or never faced any symptoms. Majority of students had moderate impact (115/31.9%), followed by severe impact (90/25%), mild impact (88/24.4%), and no impact (67/18.6%). It was observed that social support makes a good impact on the quality of life and depression among university students as it helps in improving mental health and preventing depression. There is the significant role of friends and family social support in the minimization of depression symptoms. Enhanced awareness of specified social support sources will prevent psychological diseases and mental illness among university students.